Risk Factors for Caries in Children (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Cariesogenic factors can be of different intensity and nature, different variants of their interaction contribute to the occurrence of caries, but the leading factor is the microflora of the oral cavity.